Passive solar architecture : heating, cooling, ventilation, daylighting, and more using natural flows - Bainbridge, David A.; Haggard, Kenneth L. (White River Junction, Vt. : Chelsea Green Pub., 2011)
New Buildings can be designed to be solar oriented, naturally heated and cooled, naturally lit and ventilated, and made with renewable, sustainable materials, no matter the location or climate. In this comprehensive overview of passive solar design, two of America's solar pioneers give homeowners, architects, designers, and builders the keys to successfully harnessing the sun and maximizing climate resources for heating, cooling, ventilation, and daylighting.
Includes bibliographical references and index.
Keywords: Solar energy -- Passive systems; Architecture and energy conservation